The Effect of Leadership Style and Work Discipline on Employee Performance at PT Telkom Jakarta Barat - Fajri, Chotamul; Zaanwar, Berlian Jaenuri (Journal Socio Humanities Review, 2022)
The purpose of this study was to determine the effect of leadership style and work discipline on employee performance at PT Telkom in West Jakarta, either partially or simultaneously. The method used in this study is a quantitative approach, a population of 130 people with sampling using probability sampling techniques: simple random sampling and Slovin's formula with an error level of 5% so that 99 respondents were obtained. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The result of this study is that leadership style has a significant effect on employee performance with the regression equation Y = 14,573 + 0.632X1, the correlation value of 0.646 means that the two variables have a strong relationship. The value of the coefficient of determination is 41.7%. Hypothesis test obtained t arithmetic > t table or (8.338 > 1.985). The value of the coefficient of determination is 52.5% while the remaining 47.5% is influenced by other factors. Hypothesis test obtained value of F arithmetic > F table or (52,963 > 2,700). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence of leadership style and work discipline on employee performance.